Educational Technology in Industry 6.0 - Thaariq, Zahid Zufar At; Utami, Wikan Budi; Haryono, Muhammad Budi; Benjamin Laurentino Vaz (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
The rapid development of the times requires many changes in all sectors, especially in education. Industry 6.0 is a process that occurs after discussions about the previous industrial revolution, so it is necessary to prepare education in such a way. In order to cope with this, educational technology is an important scientific basis for the facilitation of learning and the improvement of performance that is always adaptable and flexible to existing advances. The construction of educational technology, described in a narrative review, in the face of Industry 6.0 is examined in this article. Implementing educational technology as a whole needs to be built into delivering learning. This aims to optimally promote the quality of education and facilitate the ease of learning felt by all groups. In this way, this review can be an alternative point of reference to see the potential of educational technology in the face of Industry 6.0 later on.